Punishing atrocities through a fair trial : international criminal law from Nuremberg to the age of global terrorism - Hafetz, Jonathan (Cambridge : Cambridge University Press, 2018)
Over the past decades, international criminal law has evolved to become the operative norm for addressing the worst atrocities. Tribunals have conducted hundreds of trials addressing mass violence in the former Yugoslavia, Rwanda, Sierra Leone, Cambodia, and other countries to bring to justice perpetrators of genocide, war crimes, and crimes against humanity. But international courts have struggled to hold perpetrators accountable for these offenses while still protecting the fair trial rights of defendants. Punishing Atrocities through a Fair Trial explores this tension, from criticism of the Nuremberg Trials as'victor's justice' to the accusations of political motivations clouding prosecutions today by the International Criminal Court. It explains why international criminal law must adhere to transparent principles of legality and due process to ensure its future as a legitimate and viable legal regime.
Creating the template : Nuremberg and the Post-World War II international -- Prosecutions -- International criminal law's revival and the challenges of implementation -- The creation of a permanent international criminal court -- Procedure and fairness in a decentralized system -- The selectivity challenge in international criminal law -- Achieving accountability and fairness : a window into the recurring debate -- Over treating terrorism as an international crime -- Concluding remarks.
Title from publisher's bibliographic system (viewed on 24 Apr 2018).
Keywords: International criminal law; International Criminal Court; International criminal courts; Criminal liability; Fair trial; War crime trials -- Germany -- Nuremberg -- History -- 20th century; Atrocities; Terrorism